Nitric Oxide in Plants: Metabolism and Role in Stress Physiology 2014
DOI: 10.1007/978-3-319-06710-0_13
|View full text |Cite
|
Sign up to set email alerts
|

Phytohormones and Nitric Oxide Interactions During Abiotic Stress Responses

Abstract: Although nitric oxide (NO) is considered as an important signaling molecule in plants, very little is known regarding its mechanisms of action, synthesis, and possible interactions with other molecules. In the last years, NO was related to a wide array of processes in plants, which are also under the influence of the five major hormonal classes. Despite some recent advances in the knowledge of how the interaction between hormones and NO occurs, this is still a vast field for research, as many questions have ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…177 Particularly, cold is considered one of the abiotic stresses with greater efficiency in the activation of NO synthesis. 178 Although the molecular mechanism responsible for the synthesis of NO in plants is still controversial, L-arginine and nitrite are considered the main NO precursors. 179 In mammals, the major pathway of NO production is the NADPH-dependent oxidation of L-arginine to L-citrulline, catalyzed by nitric oxide synthase, although no mammalian gene homologous to this enzyme was found in plants.…”
Section: Resistance and Injury By Coldmentioning
confidence: 99%
“…177 Particularly, cold is considered one of the abiotic stresses with greater efficiency in the activation of NO synthesis. 178 Although the molecular mechanism responsible for the synthesis of NO in plants is still controversial, L-arginine and nitrite are considered the main NO precursors. 179 In mammals, the major pathway of NO production is the NADPH-dependent oxidation of L-arginine to L-citrulline, catalyzed by nitric oxide synthase, although no mammalian gene homologous to this enzyme was found in plants.…”
Section: Resistance and Injury By Coldmentioning
confidence: 99%
“…NO signaling under heat stress involves a cross talk with other signaling molecules such as cyclic adenosine diphosphate ribose, mitogen activated protein kinases, Ca 2+ , and phytohormones (Figure 2 ; Mioto et al, 2014 ; Khan M. N. et al, 2015 ; Asgher et al, 2016 ). Although, only few reports explored the link between them under heat stress, action of NO as a downstream component in hormone-mediated pathways appears to be the common factor in thermotolerance (Mioto et al, 2014 ; Asgher et al, 2016 ).…”
Section: No and Other Signaling Molecules Under Heat Stressmentioning
confidence: 99%
“…NO signaling under heat stress involves a cross talk with other signaling molecules such as cyclic adenosine diphosphate ribose, mitogen activated protein kinases, Ca 2+ , and phytohormones (Figure 2 ; Mioto et al, 2014 ; Khan M. N. et al, 2015 ; Asgher et al, 2016 ). Although, only few reports explored the link between them under heat stress, action of NO as a downstream component in hormone-mediated pathways appears to be the common factor in thermotolerance (Mioto et al, 2014 ; Asgher et al, 2016 ). A possible role for NO as a downstream component in the auxin signaling pathway has been proposed in a series of plant growth and stress responses (Pagnussat et al, 2002 ; Hu et al, 2005 ; Chen et al, 2010 ; Kolbert et al, 2012 ; Freschi, 2013 ; Asgher et al, 2016 ).…”
Section: No and Other Signaling Molecules Under Heat Stressmentioning
confidence: 99%
“…In addition to the primary role in N uptake and assimilation, the enzyme nitrate reductase has also been described to possess a nitrite-NO reductase activity that uses nitrite to produce nitric oxide (NO; Astier et al, 2018). This signaling molecule could be involved with stomatal closure in response to plant acclimation to drought (Mioto et al, 2014). Detached leaves of G. monostachia exposed for 7 days to polyethylene glycol showed that NO increased exclusively in the apical part of the leaves and the stomata remained closed even in the night period (CAM-idling mode; Mioto and Mercier, 2013).…”
Section: C3/cam-idling Comparison Through Rna-seqmentioning
confidence: 99%